2005
DOI: 10.4161/cbt.4.3.1644
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and cytokines in malignant pleural effusions secondary to mesothelioma and carcinoma

Abstract: Immunotherapy against a variety of malignancies, including pleural-based malignancies, has shown promise in animal models and early human clinical trials, but successful efforts will need to address immunosuppressive factors of the tumor and host, particularly certain cytokines and CD4(+) CD25(+) regulatory T cells (Treg). Here, we evaluated the cellular and cytokine components of malignant pleural effusions from 44 patients with previously diagnosed mesothelioma, non-small cell lung cancer (NSCLC), or breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 23 publications
3
79
0
Order By: Relevance
“…Based on our Treg cell depletion and inactivation studies it was hypothesised that the immunosuppressive cytokine transforming growth factor-beta (TGF-β) was the master regulator of Treg cell mediated immunosuppression in the AE17 murine mesothelioma model [13]. This was supported by the detection of TGF-β in mesothelioma associated pleural effusions; though it was not clear which cell type produced the cytokine [35,36]. However, although important, TGF-β alone is not solely responsible for maintaining immunosuppression in this model and thus multiple mechanisms of immunosuppression exist [12].…”
Section: Mechanisms Of Immunosuppression Exerted By Treg Cellsmentioning
confidence: 82%
“…Based on our Treg cell depletion and inactivation studies it was hypothesised that the immunosuppressive cytokine transforming growth factor-beta (TGF-β) was the master regulator of Treg cell mediated immunosuppression in the AE17 murine mesothelioma model [13]. This was supported by the detection of TGF-β in mesothelioma associated pleural effusions; though it was not clear which cell type produced the cytokine [35,36]. However, although important, TGF-β alone is not solely responsible for maintaining immunosuppression in this model and thus multiple mechanisms of immunosuppression exist [12].…”
Section: Mechanisms Of Immunosuppression Exerted By Treg Cellsmentioning
confidence: 82%
“…Their result of existence of Tregs corresponded with our study, and anti-CD25 antibody might have a potency against mesothelioma itself, because our study revealed the CD25 expression in mesothelioma cells in human lung tissue. Delong et al detected CD4+CD25+ T cells in MM pleural effusions that contained high levels of the immunosuppressive cytokine transforming growth factor-B (27). Wald et al demonstrated the accumulation of CD4+CXCR4 highCD69 T cells in lung adenocarcinoma, and these cells were considered to contribute to tumor progression by shaping the immune cell population that infiltrated the cancer tissue (16).…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study, differences in T reg -cell frequencies were shown for malignant pleural effusions from patients with mesothelioma compared with carcinomatous pleural effusions from patients with non-small-cell lung cancer or breast cancer. 79 Overall, previous work has clearly established that T reg cells are increased in most human solid tumors. Furthermore, there seems to be a stage-dependent increase of T reg cells with frequencies of T reg cells probably correlated to overall survival.…”
Section: Increased Frequencies Of T Reg Cells In Solid Cancersmentioning
confidence: 99%